Fragmentation of polymer nanocomposites: modulation by dry and wet weathering, fractionation, and nanomaterial filler. Issue 6 (21st May 2020) - Zepp, Richard; Ruggiero, Emmanuel; Acrey, Brad; Davis, Mary J. B.; Han, Changseok; Hsieh, Hsin-Se; Vilsmeier, Klaus; Wohlleben, Wendel; Sahle-Demessie, Endalkachew
Abstract : Weathering and fragmentation of polymer nanocomposites. Abstract : In recent years, an increasing number of polymeric composites incorporating engineered nanomaterials (ENMs) have reached the market. Such nano-enabled products (NEPs) present enhanced performance through improved mechanical, thermal, UV protection, electrical, and gas barrier properties. However, little is known about how environmental weathering impacts ENM release, especially for high-tonnage NEPs like kaolin products, which have not been extensively examined by the scientific community. Here we study the simulated environmental weathering of different polymeric nanocomposites (epoxy, polyamide, polypropylene) filled with organic (multiwalled carbon nanotube, graphene, carbon black) and inorganic (WS2, SiO2, kaolin, Fe2 O3, Cu-phthalocyanines) ENMs. Multiple techniques were employed by researchers at three laboratories to extensively evaluate the effect of weathering: ultraviolet-visible spectroscopy (UV-vis), Fourier transform infrared spectroscopy (FTIR), optical microscopy, contact angle measurements, gravimetric analysis, analytical ultracentrifugation (AUC), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and Raman spectroscopy. This work aimed to elucidate the extent to which weathering protocol ( i.e. wet vs. dry) and diverse filler characteristics modulate fragment release and polymer matrix degradation. In doing so, it expanded the established NanoRelease protocol, previously used for analyzing fragment emission, by evaluating two significant additions: (1) simulated weathering with rain events and (2) fractionation of sample leachate prior to analysis. Comparing different composite materials and protocols demonstrated that the polymer matrix is the most significant factor in NEP aging. Wet weathering is more realistic than dry weathering, but dry weathering seems to provide a more controlled release of material over wet. Wet weathering studies could be complicated by leaching, and the addition of a fractionation step can improve the quality of UV-vis measurements.